Ethical dilemnia of the therapeutic decisions in the care of the severe chronic anorexia nervosa: About a case. (1st November 2013) - Scolan, V.; Praline, O.; Carlin, N.; Noël, V.
Abstract : When caring for of patients suffering from severe anorexia, medical teams may feel deprived in the face of the ambivalent behavior of some of these patients who accept medical care but refuse nutrition. We present here the case of a woman suffering from severe chronic anorexia with a state of morbid malnutrition, which presented the ethical question of how to deal with this unreasonable attitude. These extreme cases raise several questions regarding avoiding malfeasance and when to provide palliative care in a management of psychiatric pathology.